Kyberšikana na střední škole - Hrádek, Tomáš; Tomáš Hrádek (České vysoké učení technické v Praze, 2022)
V bakalářské práci na téma Kyberšikana na střední škole bude prostřednictvím autorského dotazníku zjištěn a popsán tento jev. Budu specifikovat jeho formy, analyzovat motivaci k tomuto chování a navrhovat způsoby, jak kyberšikanu v daném prostředí redukovat. Bakalářská práce bude mít teoreticko-empirický charakter. V první teoretické části bude bakalářská práce zaměřena na zjištěné poznatky současné odborné literatury. Ve druhé empirické části bude kvantitativně vypracovaná sonda z prostředí střední odborné školy

The bachelor’s thesis on the topic of cyberbullying in high school will use an author’s questionnaire to identify and describe this phenomenon, specify its forms, analyze the motivation for this behavior and suggest ways to reduce cyberbullying in the environment. The bachelor thesis will have a theoretical – empirical character. In the first theoretical part, the bachelor’s thesis will focus on the findings of current literature. In the second empirical part, there will be a quantitatively surveyed probe from the environment of a seconddary vocational school.
Cyberbullying at Secondary School
Keywords: kyberšikana; šikana; agresor; oběť; přihlížející; sociální sítě; informace; legislativa; prevence; Cyberbullying; Bullying; Aggressor; Victim; Watching; Social networks; Information; Legislation; Prevention